Penerapan Pendampingan Ibu Hamil Oleh Kader Kesehatan Dengan Metode “Siska” Satu Ibu Satu Kader Sebagai Upaya Peningkatan Kualitas Kesehatan Ibu Hamil - Anik Kurniawati; Rohmi Handayani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Efforts to lower maternal and infant mortality require roles as well as cross-sectoral. Kader is the carrier of the health development mission at the lowest level. Until now, health cadres have sometimes been a reference source for dealing with a person's health problems. The process of accompanying pregnant mothers is carried out by the village maid, however in the movement of the community is not apart from the role of the cadres as the person carrying the health mission closest to the community. Objective: 1. Improve the knowledge of cadres about the support of pregnant mothers with SISKA method (one mother one cadre); 2. Improving the ability of caders in supporting pregnant Mothers with SISKA method ( satu ibu satu kader ) Method: Press test is done before health education is given, then continued with health education, demonstration as well as practical early detection of high-risk pregnant mothers. After that, we'll have a post-test. The second phase is accompanied by the pregnant woman from the third trimester, which is the age of pregnancy 28 weeks to 40 weeks. Result: Post-test results show that the number of cadres with good knowledge has increased from 80% to 90%, some cadres (90%) have implemented adhesion according to the guidelines. Conclusion: The knowledge of caders increased after getting educational education on SISKA methods, as well as caders have been able to provide support to mothers pesticides, maternity and respiratory according to the guidelines.